2015
DOI: 10.1007/s11663-015-0480-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium Study of ZnO-“FeO”-SiO2 System at Fixed Po2 10−8 atm

Abstract: Analysis of quenched copper smelting slag from the bottom blown furnace at Dongying Fangyuan Nonferrous Metals Co., Ltd. (Fangyuan) shows that significant ZnO is present in both liquid and spinel phases. Phase equilibria have been investigated in the system ZnO-Fe 2 O 3 -SiO 2 in air and system ZnO-"FeO"-SiO 2 in equilibrium with metallic iron. These conditions cannot represent copper smelting process in which oxygen partial pressure is around 10 -8 atm. In the present study phase equilibria in the system ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…Shui et al [9,10] studied the bath surface wave and mixing phenomena in the bottom blown copper smelting furnace, and provided a better understanding of the blowing patterns. Liu et al [11,12] studied the phase equilibria of the ZnO-"FeO"-SiO2 system and ZnO-"FeO"-SiO2-Al2O3 system at Po2 10 −8 atm (10 −3 Pa), which is close to the SKS smelting condition, and found that the presence of ZnO or Al2O3 in the slag significantly increased the liquidus temperature. Zhang et al [13] analyzed the gas-liquid multi-phase flows in an SKS furnace to optimize the oxygen tuyère structure parameters in the CFD (Computational Fluid Dynamics) method.…”
Section: Introductionmentioning
confidence: 97%
“…Shui et al [9,10] studied the bath surface wave and mixing phenomena in the bottom blown copper smelting furnace, and provided a better understanding of the blowing patterns. Liu et al [11,12] studied the phase equilibria of the ZnO-"FeO"-SiO2 system and ZnO-"FeO"-SiO2-Al2O3 system at Po2 10 −8 atm (10 −3 Pa), which is close to the SKS smelting condition, and found that the presence of ZnO or Al2O3 in the slag significantly increased the liquidus temperature. Zhang et al [13] analyzed the gas-liquid multi-phase flows in an SKS furnace to optimize the oxygen tuyère structure parameters in the CFD (Computational Fluid Dynamics) method.…”
Section: Introductionmentioning
confidence: 97%
“…Al-Mn-Mg 3xxx alloys are promising aluminum alloy candidates for elevatedtemperature applications (250-350°C), and great efforts have made to promote the precipitation of thermally stable dispersoids of these alloys during heat treatment and to improve their elevated-temperature properties [1][2][3][4]. It is reported that the yield strength at 300°C can reach 78 MPa in a conventional 3004 alloy or even as high as 86 MPa with a modified chemical composition after heat treatment at 375°C/48h [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the yield strength at 300°C can reach 78 MPa in a conventional 3004 alloy or even as high as 86 MPa with a modified chemical composition after heat treatment at 375°C/48h [3,4]. The most significant advantage of dispersoid-strengthening 3xxx alloys over precipitationstrengthening aluminum alloys, such as 2xxx, 6xxx and 7xxx, is their excellent thermal stability at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from Table 3 that significant amounts of Al 2 O 3 , CaO, MgO and ZnO are present in the BBF slag which can influence the liquidus temperature of the slag. Systematic studies were conducted under controlled oxygen partial pressures to evaluate the effects of these components on liquidus temperature of the copper smelting slag [32][33][34][35][36][37][38][39]. Figure 6 shows liquidus temperature as a function of Fe/SiO 2 weight ratio at Po 2 = 10 −8 atm [32].…”
Section: Phase Equilibriamentioning
confidence: 99%